Arctic political imaginaries: crafting technologies and inhabiting infrastructures. Issue 2 (3rd April 2017) - Sinclair, Katherine
Abstract : This paper seeks to address the relationship between acceptance of land use policies and differing understandings of place. Drawing on literature about technologies of the imagination and literature about infrastructure, it suggests that a synthesis of certain aspects of these two theoretical orientations produces a model that can be used to conceptually as well as practically explain the acceptance or rejection of policies. Technologies of the imagination here refer to phenomenon whose outcomes are not fully conditioned, and infrastructure acts as the underlying framework on which these technologies operate. This paper explores this relationship via a comparative case study: former Canadian federal government policy speeches; historical and contemporary popular portrayals of the 'North'; and contemporary lived Inuit experiences at a Canadian mine site. The imaginings of space are very different between the two publics that are exposed to them: the Canadian southern audience and the Inuit northern audience. This paper proposes that this disparity and policy complex is best understood as a system that works on technologies and infrastructures as creating and being constituted by imagination. This framework explains how the gap between southern policies and northern priorities persists, and why it will continue to persist in the current political system.